Les aspirations à l’assimilation à l’épreuve de la présence du bagne dans la colonie de la Guyane française (1879-1938) - Boris Lama (Caravelle)
During the second half of the 19th century, the demand for assimilation among the political actors of French Guiana was undermined by the presence of the penal colony. Our article analyzes the positions taken by prominent citizens and members of the General Council during the establishment of the Relegation (1885) and after the Great War, the elites believed that the participation of Guyanese in this conflict proves their Frenchness and justifies the removal of the penal colony.